A tale of fire-sales and liquidity hoarding - Aleksander Berentsen; Benjamin Müller (University of Zurich, Department of Economics, 2014)
We extend the analysis of the interbank market model of Gale and Yorulmazer (2013) by studying a larger set of trading mechanisms. A trading mechanism, which allows for randomized trading, restores efficiency. In contrast to Gale and Yorulmazer, we find that fire-sale asset prices are efficient and that no liquidity hoarding occurs in equilibrium. While Gale and Yorulmazer find that the market provides insufficient liquidity, we find that it provides too much liquidity.
Keywords: G12; G21; G33; D83; 330; Fire-sales; lotteries; liquidity hoarding; interbank markets; indivisibility